Knowledge sharing and organizational performance - Ang Hong Loong; Noor Fzlinda Fabeil; Pang Yeng Yuan (Kaizentrenovation Sdn Bhd, 2022)
Malaysia is one of the industrializing and emerging countries that willing to undertake the rapid economic change and investing in more productive capacity. The contribution of output and employment from the manufacturing sector has been steadily increasing, while the economy from industrial era has shifted to information era; focusing more on knowledge-based economy. Manufacturing companies in Malaysia are facing challenges and opportunities from a rapidly changing operating environment and industrial revolution, generation of new sustainable value chain systems, and contribution to the knowledge-based economy. The aim of this study is to examine the influence of tacit and knowledge sharing on organizational performance among manufacturing companies in Malaysia. This quantitative study would provide an insight on the importance and effects of tacit and explicit knowledge sharing toward organizational performance among Malaysia’s manufacturing companies. The key underpinning theory of this study is Knowledge-based View (KBV). Data were obtained from 145 manufacturing companies in Malaysia via the representative of Production Managers. This study provides fundamental knowledge and direction for researchers in further research as well as practitioners to constantly improve their organizational performance through the stimulation of tacit and explicit knowledge sharing practices.